Remembering Abdul Quadir: life and anecdotes - Hasan, Md. Mahmudul (The Daily Star, 2019)
There are certainly great men and women in every corner of Bangladesh to whom we owe the foundation of our literary and cultural life. Commemorating their lives and reading their work can help us regain our cultural confidence and independence and establish our national pride once more. Deciphering their origins and journeying through their writings have pertinent relevance to us and the next generation, as our cultural history is tied to our literary figures.